Information theory applied to numerical simulations of tokamak plasmas in a low-to-high confinement transition - Costa, Sarah Gomes da Silva Paes da (2024)
Dissertação (mestrado) — Universidade de Brasília, Programa de Pós-Graduação em Ciência de Materiais, 2024.